2009
DOI: 10.1159/000223440
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tiam1 and Rac1 Overexpression in Nasopharyngeal Carcinoma

Abstract: Purpose: This study is designed to investigate the roles of Tiam1 and Rac1 in nasopharyngeal carcinoma (NPC). Methods: NPC samples (n = 102) were analyzed with immunohistochemistry for Tiam1 and Rac1 proteins, 28 of which were also analyzed with quantitative RT-PCR and Western blots for Tiam1 and Rac1 mRNA and protein expression. The expression of Tiam1 and Rac1 in noncancerous nasopharyngeal tissue (n = 26) acted as a control. The expression was gauged regarding stage, grade and survival. Results: Tiam1 and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Tiam1 maintains the specificity of rac1 toward specific downstream effector pathways, whereas rac1 regulates cell survival and cell-cycle progression (7,8). Together, Tiam1-rac1 is a critical component in the biology of human tumors, in both transformed cells as and the cells in the tumor microenvironment (9)(10)(11). Tiam1 is a potent modifier of oncogenic Ras-induced skin tumor initiation, promotion, and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Tiam1 maintains the specificity of rac1 toward specific downstream effector pathways, whereas rac1 regulates cell survival and cell-cycle progression (7,8). Together, Tiam1-rac1 is a critical component in the biology of human tumors, in both transformed cells as and the cells in the tumor microenvironment (9)(10)(11). Tiam1 is a potent modifier of oncogenic Ras-induced skin tumor initiation, promotion, and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al recently reported that overexpression of Tiam1 was significantly correlated with vascular invasion status (P=0.02), intrahepatic metastasis status (P=0.009) and histological differentiation (P=0.008) of patients with hepatocellular carcinoma (15). In addition, Tiam1 was overexpressed in nasopharyngeal carcinoma cells and their protein up-regulation was significantly associated with stage and grading (P<0.05 for all) (12). Strong Tiam1 overexpression in prostate carcinomas relative to the respective benign prostatic epithelium was statistically significantly associated with disease recurrence (P=0.016), the presence of lymph vessel invasion (P=0.031) and high Gleason scores (GS) (27).…”
Section: Disscussionmentioning
confidence: 94%
“…Increasing evidence has focused on the regulation of Tiam1 expression, as well as the role of Tiam1 in cancer progression and metastasis that Tiam1 specifically activates Rho-like GTPases (e.g., Rac1) and Tiam1-Rac1 pathway affects the migration and invasion of many tumors, such as nasopharyngeal carcinoma (12), breast cancer (13), retinoblastoma (14) and hepatocellular carcinoma (15). Additionally, overexpression of Tiam1 in tumor cells, implying a poor prognosis, has been linked to multiple different tumors (12)(13)(14)(15). However, to date, few studies have been performed to investigate whether Tiam1 plays a major role in the occurrence and development of ESCC and whether its overexpression implies poor prognosis of the patients with ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Tiam1 maintains the specificity of Rac1 toward specific downstream effector pathways, whereas Rac1 regulates cell survival and cell cycle progression (8,9). Together, Tiam1-Rac1 is a critical component in the biology of human tumors, affecting the transformed cells themselves and the tumor microenvironment (10)(11)(12). Tiam1 is a potent modifier of oncogenic Ras-induced skin tumor initiation, promotion and progression (13).…”
Section: Introductionmentioning
confidence: 99%
“…Tiam1 is a potent modifier of oncogenic Ras-induced skin tumor initiation, promotion and progression (13). Moreover, numerous studies have demonstrated that the upregulation of Tiam1 is associated with an aggressive phenotype and a poor clinical outcome in several types of malignant tumors, including breast (14), colon (15), prostate (16), liver (17) and nasopharyngeal (11) esophageal squamous cell carcinoma (18). However, to date, the correlation between Tiam1 expression and ovarian carcinoma has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%